2020
DOI: 10.47194/ijgor.v1i3.50
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Youtube as a Learning Tool in Teaching Listening Skill

Abstract: YouTube is not only a platform that individuals share, upload, comment on videos; but also teachers and educators can make practical and effective use of it to the best as great that students can have more an advantage or profit gained. This study aims to carry out a systematic or formal inquiry to discover and examine the facts of how active and distinguished YouTube can be in the educational process and how it is beneficial for language teachers to enhance the skills of students. The study exhibits different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 6 publications
(10 reference statements)
3
47
1
1
Order By: Relevance
“…(2019, p. 101) showed that “the students' speaking skill was improving in three aspects 1) accuracy, 2) fluency, 3) performance”. Similar findings on the effectiveness of YouTube videos in improving students’ speaking skills were reported by different scholars (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ).…”
Section: Discussion Of Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…(2019, p. 101) showed that “the students' speaking skill was improving in three aspects 1) accuracy, 2) fluency, 3) performance”. Similar findings on the effectiveness of YouTube videos in improving students’ speaking skills were reported by different scholars (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ).…”
Section: Discussion Of Resultssupporting
confidence: 84%
“…Different scholars reported similar findings on the effectiveness of YouTube videos in improving students’ speaking skills (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ). Qomar (2016) examined the use of YouTube in enhancing students' speaking performance and found that YouTube could improve students' speaking skills.…”
Section: Review Of Related Literaturementioning
confidence: 73%
See 2 more Smart Citations
“…More pupils are engaged by YouTube videos, which provide a greater comprehension and satisfaction for the sensitivity of learning ability of students [21]. YouTube clips are only a simple technique to make the instructional content-related and specified, according to [22].…”
Section: Benefits Of Youtube Videos As a Learning And Teaching Platformmentioning
confidence: 99%